Effect of the rope jumping exercise in some lipid profile for the obese females participants in fitness and health programs - Ibrahim, Nashwan; Said, wasen; Farouk , intathar (Journal of Physical Education, 2010)
The effect of the rope jumping exercise in some lipid profile for the obese females participants in fitness and health programs was investigation on (10) adult obese females from Talkef secondary school , their mean Ages , Weights ,and Heights was (16 SD ±0.73 yrs),(78.5 SD ±1.34 kg),(1.58 SD ± 4.84 m) respectively . The procedures of the research included pre test (before applying the program of the rope jumping), applying the program of the rope jumping exercise(suggested from Mohamad Nasr Alden Rathwan (1984), and post test (after applying the program of the rope jumping). The test include Measuring of Total cholesterol (TC), Very low density lipoproteins cholesterol (VLDL), High density lipoprotein -cholesterol (HDL-C), Low density lipoprotein -cholesterol (LDL-C), and Triglycerides (TG) before and after applying the program of the rope jumping . This study concluded that program of the rope jumping exercise for (8) weeks causes significant decrease in Total cholesterol (TC), Very low density lipoproteins cholesterol (VLDL), Low density lipoprotein -cholesterol (LDL-C), and Triglycerides (TG). While causes significant increase in High density lipoprotein -cholesterol (HDL-C).